Enhancing Medication Safety: The Role of Community and Hospital Pharmacists in Modern Healthcare Systems - Ahmed, Rashed; TANZIMUR RAHMAN TAMIM (RADINKA JOURNAL OF HEALTH SCIENCE, 2025)
Medication safety remains a cornerstone of healthcare delivery, necessitating a comprehensive approach within community and hospital pharmacy settings. Community pharmacies serve as accessible points of care, bridging the gap between healthcare providers and patients by offering essential services such as prescription management, health counseling, and immunizations. Conversely, hospital pharmacies function within structured healthcare environments, focusing on the preparation, monitoring, and administration of complex medication regimens, often tailored to individual patient needs. This article explores the pivotal roles pharmacists play in ensuring medication safety, emphasizing their responsibilities in dispensing accuracy, patient education, and inter-professional collaboration. It highlights the challenges faced globally and in Bangladesh, including workforce shortages, regulatory inconsistencies, and technological constraints. By contrasting global best practices with the current state in Bangladesh, the discussion underscores the need for policy reforms, advanced training, and resource optimization to align local practices with international standards. The integration of emerging technologies and enhanced professional education is imperative to advance the roles of pharmacists in both community and hospital settings. A unified approach that prioritizes patient-centered care, continuous professional development, and robust regulatory frameworks can significantly enhance medication safety outcomes. This review concludes with recommendations for bridging the gap between global benchmarks and localized practices to achieve sustainable healthcare improvements.